Association between serum sphingolipids and eudaimonic well-being in white U.S. adults - Loni Berkowitz (Nature Portfolio, 2021)
Abstract Emerging research has linked psychological well-being with many physiological markers as well as morbidity and mortality. In this analysis, the relationship between components of eudaimonic well-being and serum sphingolipids levels was investigated using data from a large national survey of middle-aged American adults (Midlife in the United States). Health behaviors (i.e., diet, exercise, and sleep) were also examined as potential mediators of these relationships. Serum levels of total ceramides—the main molecular class of sphingolipids previously associated with several disease conditions—were inversely linked with environmental mastery. In addition, significant correlations were found between specific ceramide, dihydroceramide, and hexosylceramides species with environmental mastery, purpose in life, and self-acceptance. Using hierarchical regression and mediation analyses, health behaviors appeared to mediate these associations. However, the link between ceramides and environmental mastery was partially independent of health behaviors, suggesting the role of additional mediating factors. These findings point to sphingolipid metabolism as a novel pathway of health benefits associated with psychological well-being. In particular, having a sense of environmental mastery may promote restorative behaviors and benefit health via improved blood sphingolipid profiles.